Multi-targeted olink proteomics analyses of cerebrospinal fluid from patients with aneurysmal subarachnoid hemorrhage - Rui Ding; Liquan Wu; Shanshan Wei; Haoran Lu; Xiaohong Qin; Xizhi Liu; Yanhua Wang; Wen Liu; Huibing Li; Baochang Luo; Teng Xie; Zhibiao Chen (Proteome Science)
Abstract Background The complexity of delayed cerebral ischemia (DCI) after aneurysmal subarachnoid hemorrhage (aSAH) may require the simultaneous analysis of variant types of protein biomarkers to describe it more accurately. In this study, we analyzed for the first time the alterations of cerebrospinal fluid (CSF) proteins in patients with aSAH by multi-targeted Olink proteomics, aiming to reveal the pathophysiology of DCI and provide insights into the diagnosis and treatment of aSAH. Methods Six aSAH patients and six control patients were selected, and CSF samples were analyzed by Olink Proteomics (including 96-neurology panel and 96-inflammation panel) based on Proximity Extension Assay (PEA). Differentially expressed proteins (DEPs) were acquired and bioinformatics analysis was performed. Results PCA analysis revealed better intra- and inter-group reproducibility of CSF samples in the control and aSAH groups. 23 neurology-related and 31 inflammation-relevant differential proteins were identified. In the neurology panel, compared to controls, the up-regulated proteins in the CSF of SAH patients predominantly included macrophage scavenger receptor 1 (MSR1), siglec-1, siglec-9, cathepsin C (CTSC), cathepsin S (CTSS), etc. Meanwhile, in the inflammation group, the incremental proteins mainly contained interleukin-6 (IL-6), MCP-1, CXCL10, CXCL-9, TRAIL, etc. Cluster analysis exhibited significant differences in differential proteins between the two groups. GO function enrichment analysis hinted that the differential proteins pertinent to neurology in the CSF of SAH patients were mainly involved in the regulation of defense response, vesicle-mediated transport and regulation of immune response; while the differential proteins related to inflammation were largely connected with the cellular response to chemokine, response to chemokine and chemokine-mediated signaling pathway. Additionally, in the neurology panel, KEGG enrichment analysis indicated that the differential proteins were significantly enriched in the phagosome, apoptosis and microRNAs in cancer pathway. And in the inflammation panel, the differential proteins were mainly enriched in the chemokine signaling pathway, viral protein interaction with cytokine and cytokine receptor and toll-like receptor signaling pathway. Conclusions These identified differential proteins reveal unique pathophysiological characteristics secondary to aSAH. Further characterization of these proteins and aberrant pathways in future research could enable their application as potential therapeutic targets and biomarkers for DCI after aSAH.